Evidence That ‘candidatus liberibacter asiaticus’ moves predominantly toward new tissue growth in citrus plants - Raiol-Junior, Laudecir L.; Cifuentes-Arenas, Juan C.; de Carvalho, Everton V. [UNESP]; Girardi, Eduardo A.; Lopes, Silvio A. (Scientific Societies, 2021)
‘Candidatus Liberibacter asiaticus’ (Las) is an unculturable, phloem-limited, insect-transmitted bacterium associated with the Asiatic form of huanglongbing (HLB), the most destructive citrus disease. In Asia and the Americas, it is transmitted by the Asian citrus psyllid (Diaphorina citri Kuwavama). Despite considerable research, little is known about the processes involved in plant infection and colonization by Las. This study was conducted to determine whether the basal portion (below girdling) of the plant is an important route for Las to move laterally from a point of inoculation on a branch to pathogen-free branches elsewhere in the canopy, and to quantify the influence of actively growing tissues on vertical upward (acropetally) or downward (basipetally) movement of Las. Nongirdled and fully or partially girdled stems of potted plants of ‘Pera’ sweet orange, graft-inoculated above or below girdling, were sampled in distinct regions and assessed by qPCR, 6 months postinoculation. Las invaded all regions of partially and nongirdled plants but remained restricted to the inoculated regions of fully girdled plants, evidence that in planta bacterium movement is limited to the phloem. In fully girdled plants, starch accumulated above the girdling site, probably because of changes in flow of phloem sap. To study the influence of actively growing tissues, inoculated ‘Valencia’ sweet orange plants were kept intact or were top- or root-pruned to force production of new tissues, and sampled at 15-day intervals. Las migrated rapidly and most predominantly toward newly developing root and leaf tissues. The rapid and predominant movement of Las to newly developed shoots and roots would explain failures of canopy heat treatments and pruning to cure HLB-affected trees, and reinforces the need to protect rapidly growing new shoots from feeding by D. citri in order to minimize transmission and spread of the pathogen by the vector within and between orchards.
Keywords: Girdling; Huanglongbing; Liberibacter movement; QPCR